Incidence and prognostic significance of malignant arrhythmias during (repetitive) Holter electrocardiograms in patients with pulmonary hypertension - Bandorski, Dirk; Heibel, Sebastian; Höltgen, Reinhard; Bogossian, Harilaos; Ghofrani, Hossein Ardeschir; Zarse, Markus; Gall, Henning (Frontiers in Cardiovascular Medicine, 2023)
Background In patients with pulmonary hypertension (PH), increased pulmonary vascular resistance (PVR) may lead to increased right ventricular afterload and cardiac remodelling, potentially providing the substrate for ventricular arrhythmias. Studies dealing with long term monitoring of patients with PH are rare. The present study evaluated the incidence and the types of arrhythmias retrospectively recorded by Holter ECG in patients with newly detected PH during a long-term Holter ECG follow-up. Moreover, their impact on patient survival was evaluated. Patients and methods Medical records were screened for demographic data, aetiology of PH, incidence of coronary heart disease, level of brain natriuretic peptide (BNP), results from Holter ECG monitoring, 6-minute walk test distance, echocardiographic data and hemodynamic data derived from right heart catheterization. Two subgroups were analyzed: 1. patients (n = 65) with PH (group 1 + 4) and derivation of at least 1 Holter ECG within 12 months from initial detection of PH and 2. patients (all PH etiologies, n = 59) with 3 follow-up Holter ECGs. The frequency and complexity of premature ventricular contractions (PVC) was classified into “lower” and “higher” (=non sustained ventricular tachycardia, nsVT) burden. Results Holter ECG revealed sinus rhythm (SR) in most of the patients (n = 60). Incidence of atrial fibrillation (AFib) was low (n = 4). Patients with premature atrial contractions (PAC) tend to have a shorter period of survival (p = 0.098), PVC were not correlated with significant survival differences. During follow-up PAC and PVC were common in all PH groups. Holter ECG revealed non sustained ventricular tachycardia in 19/59 patients [(32.2%); n = 6 during first Holter-ECG, n = 13 during second/third Holter-ECG]. In all patients suffering from nsVT during follow-up previous Holter ECG revealed multiform/repetitive PVC. PVC burden was not linked to differences in systolic pulmonary arterial pressure, right atrial pressure, brain natriuretic peptide and results of six-minute walk test. Conclusion Patients with PAC tend to have a shortened survival. None of the evaluated parameters (BNP, TAPSE, sPAP) was correlated with the development of arrhythmias. Patients with multiform/repetitive PVC seem to be at risk for ventricular arrhythmias.